The Effectiveness Of Scaffolding-Assisted Superitem Learning Models On Student Learning Outcomes - Janah, Miftachul; Wahyuningsih, Eleonora Dwi; Rokhman, M. Shaefur (Integral (Jurnal Penelitian Pendidikan Matematika), 2024)
The aims of this research are to: (1) Describe the average learning outcomes of scaffolding-assisted superitem learning that are more than the KKM, (2) Describe the proportion of learning outcomes from learning using the scaffolding-assisted superitem model that are above the KKM of more than 70% (3) Describe The learning outcomes of the superitem learning model assisted by scaffolding are better than the conventional learning model. The population in this study were students in class VIII Odd Semester of SMP Negeri 3 Petarukan for the 2023/2024 academic year, consisting of 10 classes totaling 320 students. Samples were taken from this population using a simple random sampling probability sampling technique and one experimental class, one control class and one trial class were obtained. Data collection techniques use documentation and tests. Meanwhile, data analysis for this research uses the average test, one-party proportion test and one-party t test with a significance level of 5%. The results of this research show that: (1) the average learning outcomes of students using the superitem learning model assisted by scaffolding are more than the KKM with a KKM value of 70, (2) the learning outcomes of students using the superitem learning model assisted by scaffolding can achieve KKM exceeding 70% , (3) students' mathematics learning outcomes using the scaffolding-assisted superitem learning model are better than conventional learning models